Answer:
Then the desired equation is y = -2x - 6.
Step-by-step explanation:
As we move from point (-3, 0) to point (0, -6), x increases by 3 and y decreases by 6. Thus, the slope of the line segment connecting these two points is m = rise / run = -6/3 = -2.
Now use the slope-intercept equation of a straight line to determine the y-intercept of this line:
y = mx + b becomes 0 = -2(-3) + b, so that b = -6.
Then the desired equation is y = -2x - 6.
Check: Does (0, -6) satisfy y = -2x - 6? Is -6 = -2(0) - 6 true? YES